Standard methods for the examination of water and wastewater - Baird, Rodger B., editor; Eaton, Andrew D., editor; Rice, Eugene W., editor; American Water Works Association; Water Environment Federation (Washington, D C : American Public Health Assoc., 2017)
Includes bibliographical references